Linkages Between Advertising Value Perception, Context Awareness Value, Brand Attitude and Purchase Intention of Hygiene Products During COVID-19: A Two Wave Study - Shikha Karamchandani; Anushree Karani
The novel coronavirus, COVID-19 has affected the advertising industry in India. This study tries to gauge the purchase intention towards hygiene products during the ongoing pandemic with reference to smartphone advertising. The purpose of the study is to explore the features of smartphone advertisements like advertising value perception, context awareness value and brand attitude, pertaining to COVID-19 hygiene-related advertisement narratives. To serve the purpose, two-wave shortitudinal study was conducted at time T1, that is, lockdown period and T2, that is, unlock period in India with the help of non-probability snowball sampling. The total numbers of respondents at T1 were 311, while for T2 the total 160 respondents were contacted through online mode. At T1, the relationship between perceived advertising value and purchase intention was not established, which depicts the pandemic effect. At T2, the relationship between context awareness value, brand attitude and purchase intention was established. Further, at T1, the brand attitude did not show a mediating effect on purchase intention, but at T2, it was found to have a mediation effect on purchase intention. The study has important implications as ongoing pandemic has altered the way of living. This also has significantly impacted the advertising industry especially the hygiene products.